MEDICAL SERVICES IN GERMAN SOUTH WEST AFRICA - Bouch, R.J. (Scientia militaria : South African journal of military studies, 2012)
Great Britain declared war on Germany on 4 August 1914. Six days later the South African Government agreed to take military action against German South West Africa. On 14 September the first troops embarked, and after a successful campaign the German forces were forced to surrender on 9 July 1915. Military hospitals were established at Swakopmund, LOderitzbucht, Karibib, Windhoek and Aus. Casualties to the South African forces were